UI/UX Design Development on the Fresh Bocon Web with the Design Thinking Method to Optimize the Fresh Fish Agent Business in Kotanegara Village - Nelson Oktorija; Dedi Haryanto; Jimmie (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Kotanegara Village, fresh fish agents still tend to use traditional methods in carrying out their operations, such as manual recording and word-of-mouth promotions, Manual processes that are still relied on often lead to recording errors, delivery delays, and customer dissatisfaction. This further emphasizes the importance of developing web-based technologies to support their businesses. Limited understanding of technology and lack of access to easy-to-use digital platforms are one of the main factors The application of the design thinking method has proven to be effective in producing interface designs and user experiences that suit the needs of local customers, especially for fresh fish agents in Kotanegara Village. Through the stages of empathize, define, ideate, prototype, and test, this method is able to identify key problems in traditional businesses, create innovative web-based solutions, and test and optimize prototypes until they are ready for implementation. The result is a UI/UX design that improves operational efficiency, provides a better customer experience, and supports the digital transformation of the business, thereby driving business growth and competitiveness of fresh fish agents.